Stenus praedator sp. nov. from the Philippines and a new species group in Stenus Latreille, 1797 (Coleoptera: Staphylinidae, Steninae) - Mainda, Tobias (Zootaxa, 2020)
Stenus praedator sp. nov. (Philippines: Mindanao) is described and the S. heterocerus group is proposed. All species of the group are figured.